Project Molines: Modelling floods in estuaries. From the hazard to the critical management - Final Report - Freire, P. (2016)
The final technical report of the project “MOLINES - Modelling floods in estuaries. From the hazard to the critical management” (ref. PTDC/AAG-MAA/2811/2012) is presented. The project was funded by the Portuguese Foundation for Science and Technology (FCT - Fundação para a Ciência e a Tecnologia) and took place between 2013 and 2016. The MOLINES project aims at improving knowledge on estuarine margins inundation processes, considering different climate scenarios, and developing an approach to support risk management in terms of preventive and response measures. The outcomes included the definition of a new decision-making supporting framework and Web platform for emergency and land-use planning, based in three different spatial scales of analysis (regional, municipal and local), that fully benefited from the different skills and experience of the participant institutions and the involvement of the stakeholders.